ANALISA ORGANOLEPTIK DAN MIKROBIOLOGI AMDK DAN AMIU YANG DIJUAL SEKITAR KAMPUS UMKU - Yunita Rusidah; Lailatul Farikhah (Pascasarjana Universitas Jenderal Soedirman, 2021)
This study is intended to find the quality of bottled drinking water (AMDK) and drinking water (AMIU) sold around University of Muhammadiyah Kudus, in terms of organoleptic and microbiological parameters in drinking water according to SNI 01-3554-2006 and PMK No. 492 of 2010. The test is carried out using 10 sample of drinking water. They are 7 sample of AMDK (Ades, Airmu, Aqua, Cleo, Crystalin, Le mineral and Vit) and 3 sample of AMIU (Pasuruhan, Prambatan and Purwosari depots). The research consists of organoleptic and mikrobiologi (TPC, presence of E. coli and total coliform). The results of research shows that the organoleptik of all samples is in normal condition. Whereas, microbiologically, the TPC results before dilution were only Cleo and Ades which were suitable for consumption because they were absent from bacterial contamination. While the TPC results after dilution, testing the difference between E. Coli and Total coliform resulted in 7 samples of bottled drinking water which were safe and feasible as drinking water according to SNI 01-3553-2006 and 3 samples AMIU does not fulfil PMK No. 492/2010, as drinking water requirements.